1983
DOI: 10.1080/00480169.1983.34978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of footbathing treatments for ovine footrot using formalin or zinc sulphate

Abstract: A field trial was carried out to compare 3 topical treatments for ovine footrot. They were preliminary hoof paring with weekly footbathing either in 10% formalin, or in 10% zinc sulphate + 0.2% anionic surfactant ('Teepol'), or twice-weekly footbathing in the same zinc sulphate-surfactant mixture without hoof paring. Control sheep were not treated. Within 21 days, the number and severity of active lesions of footscald and footrot among treated sheep were substantially reduced by comparison with the controls; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
3
5
1
Order By: Relevance
“…Our results on the effectiveness of zinc sulfate footbathing, either as a weekly walkthrough or a 3-weekly 60-min soak, are similar to those reported by Skerman et al 14,15 The effectiveness of the 60-min Footrite footbathing regimen in our study was higher than in previous studies using either flocks with benign footrot 16 or 60-min footbathing every 2 weeks in flocks with virulent footrot (induced with strain A198, alone). 17 The single Footrite treatment was more effective than the 3-weekly 60-min Footrite treatment and similar to that achieved with two Footrite treatments in the study reported by Malecki and Coffey.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results on the effectiveness of zinc sulfate footbathing, either as a weekly walkthrough or a 3-weekly 60-min soak, are similar to those reported by Skerman et al 14,15 The effectiveness of the 60-min Footrite footbathing regimen in our study was higher than in previous studies using either flocks with benign footrot 16 or 60-min footbathing every 2 weeks in flocks with virulent footrot (induced with strain A198, alone). 17 The single Footrite treatment was more effective than the 3-weekly 60-min Footrite treatment and similar to that achieved with two Footrite treatments in the study reported by Malecki and Coffey.…”
Section: Discussionsupporting
confidence: 90%
“…The better result in the present study may have been because of a predominance of interdigital lesions. A 10% zinc sulfate solution used at regular intervals has been shown to cure more feet with interdigital lesions than with underrun lesions, although this was not the case when two 60‐min Footrite treatments were applied …”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…2 The percentage of feet with footrot lesions of score 1 or greater in the control sheep decreased between weeks 0 and 20; there were no footrot lesions in 96 control sheep at week 20, with 95 of these remaining asymptomatic to week 52; D nodosus was not isolated from samples taken from 87 feet of control sheep pared at week 53. Given that in previous studies, topical zinc sulphate treatments had generally failed to eradicate footrot, [8][9][10][11][12][13] these data provided anecdotal evidence that eradication was achieved not by footbathing alone, but by footbathing followed by prolonged exposure to dry conditions. However, the observation that one sheep in control group B had a score 5 lesion at week 28 suggested that whilst conceivably facilitating the effects of footbathing, the dry environment in isolation did not eradicate footrot even in those control sheep that had no clinical signs of footrot at the end of summer.…”
Section: Footbathingmentioning
confidence: 93%